The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10195-015-0369-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood metal ions after hybrid metal-on-polyethylene Exeter−Trident total hip replacement

Abstract: BackgroundMetal-on-metal total hip replacements (THRs) with large femoral heads have been associated with elevated levels of cobalt (Co) and chromium (Cr), which have been attributed to high levels of wear at the articular surface. Our unit recently published data showing a significant increase in the mean levels of Co ions in patients with a 36-mm diameter femoral head with the metal-on-polyethylene Trident−Accolade system. The aim of this study is to assess the levels of Co and Cr in the Exeter−Trident hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The search strategy is listed in Figure 1. The initial search yielded 1,224 unique articles. Ultimately, 91 articles remained for analysis (1-2-3, 8-9-10-11-12-13-14-15-16-17-18-19-20-21-22-23-24-25-26-27-28-29-30-31-32-33-34-35-36-37-38-39-40-41-42-43-44-45-46-47-48-49-50-51-52-53-54-55-56-57-58-59-60-61-62-63-64-65-66-67-68-69-70-71-…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy is listed in Figure 1. The initial search yielded 1,224 unique articles. Ultimately, 91 articles remained for analysis (1-2-3, 8-9-10-11-12-13-14-15-16-17-18-19-20-21-22-23-24-25-26-27-28-29-30-31-32-33-34-35-36-37-38-39-40-41-42-43-44-45-46-47-48-49-50-51-52-53-54-55-56-57-58-59-60-61-62-63-64-65-66-67-68-69-70-71-…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on the blood metal ion levels from Exeter stem has shown no major concern when used with 36 mm heads. 60 The thinnest second generation highly cross linked polyethylene (3.8 mm) is implanted on a 50 or 52 mm trident uncemented acetabular shell (Stryker, USA) and will articulate with a 40 mm heads while the liners in the smaller shells less than 50 mm will only articulate with 36 mm heads and are thicker. The trident uncemented acetabular shell (Stryker, USA) of size 54 mm or more have thicker second generation highly cross linked polyethylene (3.8 mm).…”
Section: Introductionmentioning
confidence: 99%